Modelling development and analysis on the Balanced Energy Networks (BEN) in London. (1st January 2019) - Song, William Hasung; Wang, Yang; Gillich, Aaron; Ford, Andy; Hewitt, Mark
Highlights: Evaluation on thermal & electrical energy performance for a Balanced Energy Network in London. BEN energy performance jointly solved by measurements and simulations. Assessment on BEN performance using a novel energy performance index: total system efficiency (TSE). Diverse effects of HP COP, HP & borehole output temperature, TSE on energy performance. Demand side response service: time of use electricity pricing used in BEN. Abstract: In the UK up to 40% of total final energy use is accounted for by the heating and hot water systems, which makes up 20% of greenhouse gas emissions. One path to low carbon heating is to electrify heat, and then meet the electricity demand via a smarter grid. This article presents a novel approach to electrifying heat based on a balanced energy network (BEN) system located at the London South Bank University (LSBU) campus. The BEN system includes borehole thermal storage, an ambient temperature heat network (heat transmission and distribution), water source heat pumps, smart hot water storage, and demand side response (DSR) service. Its thermal and electrical energy performances were mainly investigated. A novel energy performance index (TSE: total system efficiency) was also proposed and applied in assessing the performances. Several key findings were achieved as follows: (1) The TSE varied from 1.4 to 2.2 in one of the coldest months of the year, indicating a great improvement on energy efficiency. (2) The ICAX high-temperature heat pumps in BEN operate with a higher COP fluctuating between 3.1 and 3.2 with a Carnot efficiency of 0.5. (3) With an acceptable level of thermal comfort, the BEN system can reduce CO2 emissions up to 3.62 t for two weeks. (4) Corresponding with the initial design setting, 70 °C has been proved as the optimal operating output temperature of heat pump.